Knowledge and Attitude Regarding Complete Denture Diagnosis and Fabrication among Dental Students of BPKIHS - Shrestha, Ashish; Bhagat, Tarakant; Agrawal, Santosh Kumari; Gautam, Ujwal; Budha, Lanka; Sah, Bijay Kumar; Rawat, Arjun; Khanal, Bibhash; Pandey, Suveksha (Journal of BP Koirala Institute of Health Sciences, 2025)
Background: Every future dental surgeon must be competent enough to diagnose and prepare a treatment plan for an edentulous patient. They must learn and improve their confidence in the essential clinical and laboratory procedures for complete denture fabrication. This study aimed to evaluate the knowledge and attitude toward complete denture diagnosis and fabrication among dental undergraduates and interns in B.P. Koirala Institute of Health Sciences. Methods: A questionnaire- based cross- sectional study was conducted among dental undergraduate students (fourth year, final year and interns) of B.P. Koirala Institute of Health Sciences between February and March 2024. A self- administered questionnaire was used to assess the knowledge and attitude of complete denture diagnosis and fabrication. The scores obtained from each question were analyzed using SPSS version 26 for statistical analysis. Results: Ninety participants were included in the study. About 80% of participants obtained consent before proceeding with the treatment. The majority (95.5%) knew the primary impression technique. Most of them (65.5 %) preferred sectional border molding and used a Fox plane for determining occlusion. All of them gave post-insertion instructions after inserting the denture. Conclusion: The majority of students have developed an understanding of most of the important procedures and materials that are essential for successful denture therapy. However, they seem to lack knowledge about metal denture bases and recording the posterior palatal seal area.